PENGARUH PEMBERIAN CENDAWAN LECANICILLIUM LECANII TERHADAP MORTALITAS ULAT GRAYAK (SPODOPTERA LITURA)SECARA IN VITRO - SUHAIRIYAH, (Universitas Negeri Surabaya, 2013)
Armyworm is one of the important pests of soybean. Entomopathogenic fungi is one of alternative biological agent to control soybean pests such as armyworms. This study aimed to determine the effect of Lecanicillium lecanii on armyworm mortality and the effective concentration of Lecanicillium lecanii to infect armyworms. The design of experiment was a completely randomized design (CRD). The study consisted of 27 treatments with 3 kinds of conidial density, i.e. 107, 108, and 109 conidia/ml. Each treatment repeated 9 times. Observed data were the mortality percentage of larvae and weight of residual feed after 7 days, analyzed using one-way analysis of variance (one-way ANOVA). The results showed that the fungi affects the armyworm mortality. The effective density was 108 and 109 conidia/ml  that could kill armyworms up to 80% and 83%.   Key words: Lecanicillium lecanii; mortality of armyworms